Four cases report: Treatment of knee joint cartilage defects using autologous chondrocyte patch implantation - Wang, Le; Li, Han; Cao, Yiguo; Song, Cheng; Chen, Qi; Hao, Jun; Zhang, Weiguo; Tian, Kang (Frontiers in Surgery, 2022)
Introduction Autologous chondrocyte implantation (ACI) is a crucial method for the treatment of defects in articular cartilage. However, the extant methods for the preparation of autologous chondrocyte patch are relatively complicated and money-consuming. What is more, studies of Chinese patients are scarce. An efficient, reliable, easy-to-follow, and cost-effective technique is needed to overcome constraints. This case report aims to introduce an autologous chondrocyte patch fabrication technique to repair knee joint cartilage defects and report our typical cases with a 2-year follow-up. Case presentation We described four cases in which patients complained of knee joint pain. According to radiological examination, the patients were diagnosed as knee joint cartilage defect. Arthroscopy and autologous chondrocyte patch implantation were performed as well as a 2-year follow up of patients. The autologous chondrocyte patch for knee joint cartilage repair was fabricated using a “sandwich” technique. The preoperative and postoperative knee function was evaluated by four subjective evaluation systems. MRI was performed for all patients to achieve more intuitionistic observation of the postoperative radiological changes of defect sites. The quality of repaired tissue was evaluated by Magnetic Resonance Observation of Cartilage Repair Tissue (MOCART). Postoperative follow-up showed improvement in clinical and MOCART scores for all patients. However, one patient complained of knee joint pain after walking for a long time or recreational activities from 12-month to 18-month postoperatively. The location of pain for this patient was not in accordance with the location of cartilage defect. Conclusion The patients undergoing autologous chondrocyte patch implantation demonstrated clinical improvement and good quality of repaired tissue postoperatively. The procedure is an efficient and cost-effective treatment for knee joint cartilage defect in this report. In addition, patients with osteoarthritis carry the risk of a poor outcome after the procedure, and whether to have a procedure should be considered carefully.